Innate-like B cells - Kearney, John F. (Henry Stewart Talks, 2012)
Introduction to B cells, Innate-like B cells, Origin and function of innate-like B cells, Targets of Innate-like B cell derived antibody, Anatomy of Innate-B cell organ distribution, Human Innate-like B cells and possible clinical applications